2021
DOI: 10.21203/rs.3.rs-175664/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcriptome Characterization of Panax Quinquefolius L. seedlings in Response to Arbuscular Mycorrhizal Fungi using RNA-seq

Abstract: Panax quinquefolius L. has been considered as an important traditional Chinese medicine with a history of more than 300 years in China. Ginsenoside is the main bioactive component. Our research group has found that the accumulation of ginsenoside could be affected by arbuscular mycorrhizal fungi (AMF). However the underlying mechanism how AMF affected the biosynthesis of ginsenoside in P. quinquefolius is still unclear. In this study, the RNA-seq analysis was used to evaluate the effects of AMF (Rhizophagus in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…Figure 9(a) presents the C-V characteristic curves of artificial muscle with different levels of CLC added. The C-V characteristic curves of all five ratios of artificial muscles exhibited a rectangular-like closed structure, which indicated that the artificial muscles themselves had good charging and discharging characteristics [35]. However, we can observe that the closed graph formed by the characteristic curve of C-V is not a beautiful rectangular curve, and there are even obvious peaks.…”
Section: Electrochemical Experimentsmentioning
confidence: 83%
“…Figure 9(a) presents the C-V characteristic curves of artificial muscle with different levels of CLC added. The C-V characteristic curves of all five ratios of artificial muscles exhibited a rectangular-like closed structure, which indicated that the artificial muscles themselves had good charging and discharging characteristics [35]. However, we can observe that the closed graph formed by the characteristic curve of C-V is not a beautiful rectangular curve, and there are even obvious peaks.…”
Section: Electrochemical Experimentsmentioning
confidence: 83%
“…Table 9. Three kingdoms of Archaea on the basis of phylogenetically divisions (Barns et al, 1996;Luo and Wasserfallen, 2001;Reysenbach et al, 2000) 1-The Crenarchaeota which comprise most of the hyperthermophiles including the hyperthermophilic genera Thermoproteus and Pyrodictium as well as the thermoacidophilic genera Sulfolobus, Acidianus and Desulfurococcus.…”
mentioning
confidence: 99%